Some changes in the spatial characteristics of tourism in Slovenia since its independence - Dejan Cigale (Journal of Geography, Politics and Society, 2019)
The paper discusses the processes and changes in Slovenian tourism in the last three decades, after the disintegration of Yugoslavia. They have been related to the influence of factors both within the field of tourism and outside of it (external factors, such as geopolitical events, economic changes and shocks, etc.). Empirical analysis is focused particularly on the spatial characteristics of tourism, with the emphasis on the geographical origin of tourist flows and, on the other hand, stability/variability of geographical distribution of tourism within Slovenia. In regard to the latter, especially a very intense growth of tourist numbers in Slovenian capital (Ljubljana) is worth mentioning. The most evident change regarding inbound tourist flows is a strongly increased number of non-European tourists. The observed changes point out the fact that Slovenian tourism is increasingly embedded into globalization processes. Despite the growth in non-European tourist arrivals, the relatively short-distance tourist flows still prevail in the majority of Slovenian tourist destinations. They are also less sensitive to economic and political shocks and they will most probably remain crucial for Slovenian tourism.